PENYALAHGUNAAN NARKOBA DI KALANGAN REMAJA DALAM PERSPEKTIF ISLAM - masjkur, muhammad (Universitas Nahdlatul Ulama Sunan Giri, 2017)
Indonesia is threatened by the danger of drugtrafficking (narcotics, psychotropic and other addictive substances) and its misuse. In the perspective of Islam, the drugtrafficking synonymous with the wine (Al Khamr). It is banned for users, dealers, and manufacturers. Drugtrafficking and its misuse is dangerous because it can affect the nervous system, resulting in addiction and dependence. Drugs lead to changes in behavior, feeling, perception, and consciousness. In the perspective of Islam, there are three important things to consider in order to prevent the dissemination of drugs, namely: increasing piety of each individual community to God, to enforce the criminal justice system consistent implementation, and recruiting law enforcement officials are cautiousKeywords: Parents, interest in reading, children.